Eksplorasi Hak Asasi Manusia Melalui Prinsip-Prinsip Demokrasi - Liya Pransiska; Gunawan Santoso; Eva Monalisa Vebry Kusuma; Arif Aziz Firmansyah (Jurnal Pendidikan Transformatif, 2023)
This research aims to explore the complex relationship between human rights and democratic principles, as well as an attempt to understand how individual rights can be guaranteed and protected in the context of a democratic system. Within this framework, research highlights the importance of collaboration between government and society in creating a just and inclusive environment. This research emphasizes the close relationship between human rights and democracy as fundamental pillars in the formation of a democratic society. The main focus is given to the need for public awareness of individual rights and how democratic principles can be a means of protecting and advancing human rights. The government's central role in creating policies and mechanisms that support human rights is a major highlight. This includes developing policies that support democratic principles, effective legal protection, and transparency in decision making. Active community participation, both through public dialogue forums and complaint mechanisms, is recognized as a key element for monitoring and influencing policy implementation. Protection of the rights of vulnerable groups such as children, women and minorities is an important focus in this research, highlighting the need for policies that are inclusive and sensitive to cultural context. By exploring case studies, this research provides insights into best practices in protecting human rights in democratic contexts. The conclusions emphasize the need for continuous monitoring and evaluation of policies and programs to ensure adaptation to change and continuous improvement in human rights protection. The results of this research can provide guidance for governments, civil society, and international institutions in strengthening legal frameworks and practices that support human rights in democratic societies.